Pengembangan Komitmen Organisasi Melalui Profesionalisme Karyawan dan Kepemimpinan yang Efektif - Ernawati Ernawati; Ella Anastasya Sinambela; Rahayu Mardikaningsih; Didit Darmawan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The goals of each company will be achieved with a strong organizational commitment. Strengthening organizational commitment has the assignment of employee professionalism and appropriate leadership. The intention of this study was to affect the assignment of employee professionalism and leadership to organizational commitment. This study uses the census method with a sample of 152 respondents who are employees of a company in Gresik City. This study handling by multiple linear regression. This result of study suggest that employee professionalism will significantly shape organizational commitment. In addition, organizational commitment is also significantly influenced by the right leadership. Furthermore, employee professionalism and leadership are factors to form organizational commitment.